(untitled) (Research, Society and Development, 2022)
Scientific communication validates scientific research. When choosing a journal, the researcher should consider several aspects of the journal, such as scope, periodicity, impact factor, acceptance time, among other aspects. This research selected Brazilian journals from the Teaching Area classified in the period 2013-2016 as Qualis A1, A2 and B1 (index H5≥20). A check of each article published in the biennium 2019/2020 was performed to obtain the time between submission and acceptance (TSA) in days of the manuscript. In addition to this information, other data that could influence TSA were collected. Descriptive statistics and nonparametric test for correlation analysis were used. The total sample consisted of 5,284 articles. In 2020, the lowest average TSA observed was 28 days in a Qualis A2 journal and the highest average TSA (477 days) occurred in a Qualis B1 journal. More than half of the journals were from universities; the lowest TSA was identified among journals without publication fees; the most common periodicity was quarterly; a positive correlation was shown between number of editors and TSA in B1 journals. The results suggest that the difference in TSA observed in the biennium may be related to the paralysis in university activities due to the Covid-19 pandemic.